School Quality and Residential Property Values: Evidence from Vancouver Rezoning - Ries, John; Somerville, Tsur (The Review of Economics and Statistics, 2010)
This study utilizes changes in the catchment areas of public schools in Vancouver, British Columbia, to measure the residential price capitalization of school quality. Specifications that employ repeat sales methods to control for time-invariant neighborhood effects and disaggregated price indexes to capture time-varying neighborhood price appreciation reveal significant effects of secondary school performance on residential prices. However, when we add controls for long-run price trends in rezoned areas, only prices of residences likely to be purchased by high-income families appear to have been affected by changes in school quality induced by rezoning.